Possible cleavage sites of glutelin partial degradation confirmed by immunological analysis in globulin‐less mutants of rice (Oryza sativa L.). Issue 20 (1st August 2017) - Khan, Nadar; Yamaguchi, Satoru; Katsube‐Tanaka, Tomoyuki
Abstract: Proteolytic cleavage or partial degradation of proteins is one of the important post‐translational modifications for various biological processes, but it is difficult to analyze. Previously, we demonstrated that some subunits of the major rice ( Oryza sativa L.) seed storage protein glutelin are partially degraded to produce newly identified polypeptides X1‐X5 in mutants in which another major seed storage protein globulin is absent. In this study, the new polypeptides X3 and X4/X5 were immunologically confirmed to be derived from GluA3 and GluA1/GluA2 subunits, respectively. Additionally, the new polypeptides X1 and X2 were at least in part the α polypeptides of the GluB4 subunit partially degraded at the C‐terminus. Simulated 2D‐PAGE migration patterns of intact and partially degraded α polypeptides based on the calculation of their MWs and pIs enabled us to narrow or predict the possible locations of cleavage sites. The predicted cleavage sites were also verified by the comparison of 2D‐PAGE patterns between seed‐extracted and E. coli‐expressed proteins of the intact and truncated α polypeptides. The results and methodologies demonstrated here would be useful for analyses of partial degradation of proteins and the structure–function relationships of rice seed protein bodies.